Luto paterno: a revisão integrativa da literatura brasileira acerca do pai que perdeu seu filho por causa externa - Teixeira, Thais (2020)
Deaths from external causes happen due to accidents and violence, and the most victimized profile is made up of young, male and black people. There is a discussion about how the father of this risk profile experiences grief over the loss of a child under these circumstances. Because of the difficulty that exists to deal with the unexpected death of a child, this thesis aimed to accomplish an integrative Brazilian studies review on fatherly grief due to external causes. With regard to this matter, the grief and suffering that are developed are mostly associated with the victims’ mothers, giving them increased focus when compared to the father, who is neither socially presented nor bereaved under these circumstances, or is subordinated to the mother’s suffering. Regarding paternity and male identity, there is still a dissociation of parental roles according to gender, in a way that the grieving process suffer with the social and personal restriction of expression of feelings for the bereaved person when it comes to the death of a child. For the selection of the studies, the following databases were used: PsycInfo, PubMed, Bireme - BVS, Biblioteca Digital Brasileira de Teses e Dissertações [Brazilian Digital Library of Theses and Dissertations] (BDTD), Repositório Institucional da Fiocruz [Fiocruz Institutional Repository] (ARCA), Portal of journals of the Coordination for Improvement of Higher Education Personnel (CAPES) and Google Scholar. This is an underdeveloped theme in national research: four studies that approach the theme were found. The analysis of the selected studies identified an appreciation of the bereaved parents by the support of people who went through the same situation. The underdevelopment of this topic and the need of further studies are highlighted